The Short-Term Impact of Higher Food Prices on Poverty in Uganda - Simler, Kenneth R. (World Bank, Washington, DC, 2016)
World prices for staple foods increased between 2006 and 2008, and accelerated sharply in 2008. Initial analysis indicated that the adverse effects of higher food prices in Uganda were likely to be small because of the diversity of its staple foods, high level of food self-sufficiency, and weak links with world markets. This paper extends the previous analyses, disaggregating by regions and individual food items, using more recent price data, and estimating the impact on consumption poverty. The analysis finds that poor households in Uganda tend to be net buyers of food staples, and therefore suffer welfare losses when food prices increase. This is most pronounced in urban areas, but holds true for most rural households as well. The diversity of staple foods has not been an effective buffer because of price increases across a range of staple foods. The paper estimates that both the incidence and depth of poverty have increased -- at least in the short run -- as a result of higher food prices in 2008, increasing by 2.6 and 2.2 percentage points, respectively. The increase in poverty is highest in the Northern region, which is already the poorest in Uganda. The need for mitigating social protection measures appears to be greater than previously recognized. Not only are the negative impacts larger, but they are also much more widespread geographically. This suggests the need for continued close monitoring of the situation, including monitoring the adequacy of existing safety nets and feeding programs.